The ATP Binding Cassette Transporter Gene CgCDR1 from Candida glabrata Is Involved in the Resistance of Clinical Isolates to Azole Antifungal Agents - Sanglard, Dominique (American Society for Microbiology, 1999)
The resistance mechanisms to azole antifungal agents were investigated in this study with two pairs of Candida glabrata clinical isolates recovered from two separate AIDS patients. The two pairs each contained a fluconazole-susceptible isolate and a fluconazole-resistant isolate, the latter with cross-resistance to itraconazole and ketoconazole. Since the accumulation of fluconazole and of another unrelated substance, rhodamine 6G, was reduced in the azole-resistant isolates, enhanced drug efflux was considered as a possible resistance mechanism. The expression of multidrug efflux transporter genes was therefore examined in the azole-susceptible and azole-resistant yeast isolates. For this purpose, C. glabrata genes conferring resistance to azole antifungals were cloned in a Saccharomyces cerevisiae strain in which the ATP binding cassette (ABC) transporter gene PDR5 was deleted. Three different genes were recovered, and among them, only C. glabrata CDR1 (CgCDR1), a gene similar to the Candida albicans ABC transporter CDR genes, was upregulated by a factor of 5 to 8 in the azole-resistant isolates. A correlation between upregulation of this gene and azole resistance was thus established. The deletion of CgCDR1 in an azole-resistant C. glabrata clinical isolate rendered the resulting mutant (DSY1041) susceptible to azole derivatives as the azole-susceptible clinical parent, thus providing genetic evidence that a specific mechanism was involved in the azole resistance of a clinical isolate. When CgCDR1 obtained from an azole-susceptible isolate was reintroduced with the help of a centromeric vector in DSY1041, azole resistance was restored and thus suggested that a trans-acting mutation(s) could be made responsible for the increased expression of this ABC transporter gene in the azole-resistant strain. This study demonstrates for the first time the determinant role of an ABC transporter gene in the acquisition of resistance to azole antifungals by C. glabrata clinical isolates.